Accurate stacking engineering of MOF nanosheets as membranes for precise H2 sieving - Wufeng Wu; Xitai Cai; Xianfeng Yang; Yanying Wei; Li Ding; Libo Li; Haihui Wang (Nature Communications)
Abstract Two-dimensional (2D) metal-organic framework (MOF) nanosheet membranes hold promise for exact molecular transfer due to their structural diversity and well-defined in-plane nanochannels. However, achieving precise regulation of stacking modes between neighboring nanosheets in membrane applications and understanding its influence on separation performance remains unrevealed and challenging. Here, we propose a strategy for accurately controlling the stacking modes of MOF nanosheets via linker polarity regulation. Both theoretical calculations and experimental results demonstrate that a high linker polarity promotes neighboring nanosheets to a maximum AB stacking due to steric hindrance effects, leading to a controlled effective pore size of the membrane and consequently to improved molecular sieving. Among series of CuBDC-based 2D MOFs with different linkers, the CuBDC-NO2 nanosheet membranes exhibit a reduced effective stacking aperture of 0.372 nm, yielding H2 permeance of 4.44 × 10−7 mol m−2 s−1 Pa−1 with a high H2/CO2 and H2/CH4 selectivity of 266 and 536, respectively. This work represents the in-depth investigation of the accurate tuning of MOF nanosheet stacking in the field of 2D materials, offering more perspectives for broader applications with universality for various 2D materials.